Pengaruh Pembelajaran Berbasis STEM terhadap Kemampuan Sains Siswa di MI Negeri 3 Halmahera Utara - Ali , Nurlaila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
STEM (Science, Technology, Engineering, and Mathematics) based learning has become an innovative approach in improving science understanding at the primary level. This approach aims to provide a more contextualised, interactive and problem-solving based learning experience. However, at MIN 3 North Halmahera, science learning still faces challenges, such as the lack of student engagement in experiments and the dominance of conventional learning methods. This study aims to analyse the effect of STEM learning on students’ science skills and identify challenges in its implementation. The method used was Classroom Action Research (PTK) with two cycles, involving observation, written tests, and interviews with teachers and students. The results showed that STEM learning improved students’ understanding of science concepts, experimental skills and interest in learning science. Students become more active in exploration and able to connect theory with real applications. However, STEM implementation faces obstacles such as limited laboratory facilities and teacher readiness. Therefore, additional strategies and support from various parties are needed to ensure the effectiveness of STEM learning in improving the quality of science education in primary schools